The effect of fit between manufacturing strategy, strategic orientation, and marketing strategy on business performance - Yue-Yang Chen; I-Jen Wu; I-Chen Tsai (International Journal of Management, Economics and Social Sciences (IJMESS), 2018)
As the world has become closer and increasingly connected, business competition becomes more aggressive. As a result, marketing which has evolved for decades becomes so vital that no company can survive without it. Though marketing strategy and manufacturing strategy are organizationally separate in most firms, without a coordination of these two functional entities, an organization's survival in the market could potentially be jeopardized. Research has proved that these dimensions have a significant impact on organizational performance. Yet there is very little research being done from a holistic perspective in examining the fit relationship between marketing, manufacturing, and business strategy. Therefore, this research tries to look at those dimensions from a fit as covariation perspective. A fit model was proposed and exemplified using empirical data collected from Taiwan's top ranking companies in the manufacturing and service industry. Findings showed that the fit between marketing strategy, manufacturing strategy, and strategic orientation has a significant and positive effect on organizational performance.
Keywords: L69; M31; 330; Fit; marketing strategy; manufacturing strategy; strategic orientation; fit as covariation